Studies on the Multiplication of Apple Clonal Rootstock, Merton 793 through Cuttings - Negi, Ajender; Sharma, D. D.; Thakur, Manish; Babita (International Journal of Bio-resource and Stress Management, 2015)
The present investigation was conducted at Apple and Pear experimental block, Department of Fruit Science, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan (HP) under the net house during 2010-2011. The experiment was laid out in RBD design with three replications per treatment. There were in all ten treatments comprising of IBA application (three concentrations) and its combination with a basal wounding of cuttings (two procedures). IBA was used at 1000, 2000 and 3000 ppm and wounding treatments included i) basal split and ii) vertical incision. In all there were nine combinations of IBA and wounding treatments and compared with control. The results obtained from the study revealed that highest percentage of rooted cuttings (46.66%), number of main roots per cutting (15.67), length of main roots (29.46 cm), diameter of main roots (3.84 mm), total root length (5.37 m), fresh weight of roots (9.17 g), dry weight of roots (4.90 g), length of main shoot (125.30 cm), diameter of main shoot (171.8 mm), fresh weight of shoots (80.67 g), Dry weight of shoots (45.83 g), shoot to root ratio (0.106), total number of leaves (134.7), leaf area (43.01 cm2), total phenol content (24.37 mg g-1), C: N ratio (58.78) and total sugar content (27.50 mg g-1) were recorded in the cuttings treated with IBA 2000 ppm+Basal split.